MAKNA MEPRANI DI DESA ADAT SEMPIDI DALAM AJARAN TATTWA HINDU - Ni Luh Widya Kesuma Dewi (Widya Aksara : Jurnal Agama Hindu, 2026)
Abstract The Meprani Tradition is a religious tradition still practiced by the Sempidi community as part of a series of ceremonies at the Khayangan Tiga Temple. From the perspective of Tattwa Hindu teachings, this study examines the meaning of the Meprani Tradition. This research employed a qualitative, descriptive approach, employing observation, interviews with traditional leaders and figures, and literature review. The results indicate that the Meprani Tradition embodies the meaning of Sraddha and Bhakti, reflected in the community's sincerity in making offerings in the form of gebogan (a type of sacred offering) without the pressure of a large ceremonial offering. This tradition is also a way to carry out Dewa Yadnya (the offering of God). Meprani also reflects the application of the Tri Hita Karana concept, which is the harmonious relationship between humans, God, fellow humans, and nature. The involvement of all traditional communities across generations makes the Meprani Tradition a means of spiritual education and the ongoing transmission of religious values. Thus, this tradition serves not only as a cultural heritage but also as a reinforcement of Tattwa Hindu teachings in the lives of the Sempidi community. Keywords: Meprani; Tattwa Hindu; Sempidi Traditional Village; Tri Hita Karana; Sraddha and Bhakti; Yadnya